Research of Load and Contact Capacity of Micro-Segment Gear based on ARAMIS System - Huang Kang; Dong Yu; Liu Peng; Huang Qingqing (Jixie chuandong)
At present,there are not unified formula for static strength to calculating the gear load and contact capacity of micro-segment gear,and also no specific research and analysis for gear load and contact capacity.By using the non-contact strain measurement system ARAMIS,the contact stress of the micro-segment gear under the condition of static loading is measured,and under the same experiment condition,the strain analysis of the location near the gear mesh point and tooth root of micro-segment gear and involute gear are respectively carried out,the principal strain figure of the gear end face is obtained.The force analysis of location selection on the same point of the two kinds of gear tooth profile are carried out,and the force condition of the two kinds of gear tooth profile are compared.